AGN JET AND THERMAL CONDUCTION IN COOLING FLOW CLUSTERS - Bibi, F; Binney, J (2008)
We consider the effect of thermal conduction along with AGN jet feedback on the intracluster medium (ICM) in cooling flow clusters. A series of three-dimensional AMR hydrodynamic simulations has been carried out to analyze the dynamic of such interaction. We show the limit of applicability of the Spitzer thermal conduction during jet/ICM interaction. © 2008 World Scientific Publishing Company.